The impact of strength training on skeletal muscle morphology and architecture in children and adolescents with spastic cerebral palsy: A systematic review - Gillett, J.; Boyd, Roslyn; Carty, C.; Barber, L. (Pergamon Press, 2016)
Aim: The aim of this study was to systematically review the current literature to determine the impact of strength training on skeletal muscle morphology and architecture in individuals aged 4-20 years with spastic type cerebral palsy. Methods: A comprehensive search for randomised and non-randomised controlled trials, cohort studies and cross-comparison trials was performed on five electronic databases. Included studies were graded according to level of evidence and assessed for methodological quality using the Downs and Black scale. Quantitative data was analysed using effect sizes. Results: Six of 304 articles met the inclusion criteria. Methodological quality of the included papers ranged from 14 to 19 (out of 32). A large effect was found on muscle cross-sectional area following strength training, with small to moderate effects on muscle volume and thickness. Conclusion and implications: There is preliminary evidence that strength training leads to hypertrophy in children and adolescents with CP. A paucity of studies exist measuring morphological and architectural parameters following strength training in these individuals. Overall low study methodological quality along with heterogeneous study design, dissimilar outcome measures, and lack of adequate control groups, indicated that care is needed when interpreting the results of these studies in isolation.